2017
DOI: 10.1007/s00520-017-3917-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and reasons for treatment abandonment among children with lymphoma in Malawi

Abstract: These findings highlight families at risk for treatment abandonment, underlying reasons, and opportunities to improve retention in care for pediatric cancer patients in SSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 17 publications
4
46
0
Order By: Relevance
“…Geographical factors such as the place of residency and the time needed to travel to a referral facility have been described by some studies as important factors for abandonment, whereas other studies have found this factor to be inconsistent . This study shows that children living in a rural setting had a significantly increased risk of treatment abandonment, as previously described by other authors .…”
Section: Discussionsupporting
confidence: 81%
“…Geographical factors such as the place of residency and the time needed to travel to a referral facility have been described by some studies as important factors for abandonment, whereas other studies have found this factor to be inconsistent . This study shows that children living in a rural setting had a significantly increased risk of treatment abandonment, as previously described by other authors .…”
Section: Discussionsupporting
confidence: 81%
“…Eighteen studies met our inclusion criteria for the systematic review (Table 1). 29,32,33,35,40,41,[49][50][51][52][53][54][55][56][57][58][59][60] Two studies 41,51 were subsequently excluded from the meta-analysis because they did not report data necessary to determine sex-disaggregated rates of treatment abandonment.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have applied such data to examine factors influencing equity in service uptake and rates of treatment abandonment in childhood cancers generally. 7,8,10,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] Very few studies, however, have specifically examined association between sex and abandonment rates. 42 There is a need to fill this evidence gap to guide health system planners in a gender-sensitive approach to the implementation of cancer control programs and ensure that, in the pursuit of universal health coverage, girls with cancer are not left behind.…”
mentioning
confidence: 99%
“…Many households experience cancer diagnoses when they would expect to be at their most economically productive 4 . For the few patients who are able to access potentially curative cancer therapy, treatment abandonment rates are high 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…This has been changed to 'treatment abandonment' as follows: Pg. 3 For the few patients who are able to access potentially curative cancer therapy, treatment ○ abandonment rates are high 5,6 .' There is a comma missing following 'health' in the Lancet quote (paragraph 2 A comma has been inserted: Pg.…”
Section: Introductionmentioning
confidence: 99%